Lysosomal‐targeted anticancer half‐sandwich iridium(III) complexes modified with lonidamine amide derivatives. (27th February 2020) - Xie, Yongkang; Zhang, Shumiao; Ge, Xingxing; Ma, Wenli; He, Xiaolin; Zhao, Yao; Ye, Juan; Zhang, Hongmin; Wang, Anwei; Liu, Zhe
Abstract : Ten half‐sandwich iridium complexes containing lonidamine amide derivatives were synthesized and characterized. Unlike lonidamine, which acts on mitochondria, its iridium complexes successfully targeted lysosomes and induced lysosomal damage. Antiproliferation studies showed that most of the complexes have higher anticancer activity against A549 and HeLa cells than cisplatin. The antitumor activity of complex 6 is 2.69 times that of cisplatin against A549 cells. We also performed antitumor tests on ligands L1 and L5, and proved that they exhibit excellent antitumor activity only after binding to the metal center. The bovine serum albumin (BSA) binding test showed that the complexes had the ability to bind to BSA, and they interact with BSA by a static mechanism. The complexes can also cause changes in mitochondrial membrane potential and can produce active oxygen species better than active control. NADH/NAD + transformation experiments were used to determine if the production of ROS was caused by the transformation of NADH/NAD + . We also explored the way that the complexes enter cells. Abstract : Design and synthesis of ten half‐sandwich iridium complexes containing ligands of lonidaminamide derivative. Flow cytometry and two‐photon laser microscopy were used to detect the microenvironment of drug action. Complexes were showed to promote apoptosis by targeting lysosomes.